Risiko Perdarahan Saluran Cerna pada Pasien COVID-19 berdasarkan Jenis Obat Antivirus di Rumah Sakit Umum Pusat Dr. M. Djamil Padang - Arnelis, Arnelis; Miro, Saptino; Zubir, Nasrul; Yoga, Vesri; Kurniawan, Andry; Kam, Alexander; Rahimi, Abdul Alim; Ranazeri, Jersivindo; Fahrurozi, R. Ifan Arief (Faculty of Medicine, Universitas Andalas, 2022)
Coronavirus disease 2019 (COVID-19) has become a global pandemic to date. Some studies reported gastrointestinal tract (GIT) bleeding occurs in several patients hospitalized with COVID-19. Medications known to be associated with an increased risk of GIT bleeding were not associated with GIT bleeding in COVID-19 patients. Objectives: To examined the risk of gastrointestinal tract (GIT) bleeding in COVID-19 patients based on antiviral drugs at Dr. M. Djamil General Hospital Padang. Methods: A nested cohort study was conducted in Dr. M. Djamil General Hospital Padang from May until October 2021. All COVID-19 patients who received antiviral drugs with GIT bleeding with onset days 0 - 7 were included. COVID-19 was confirmed by RT-PCR swab. Data entry and analysis were conducted by computerized. Results: 30 patients were involved in this study. 43,3% COVID-19 Moderate stage and 56,7% Severe stage. 63,3% were treated with remdesivir and 36,7% were treated with favipiravir. Onset on GIT tract bleeding at day 4 (23,3%), day 5 (26.7%), day 6 (30%), and day 7 (20%). The Chi-square test to determine the factors associated with GIT bleeding in COVID-19 patients including COVID-19 severity, type of antiviral drugs, anticoagulant, and corticosteroid revealed that none of all potential factors above related to GI bleeding. Conclusion: The type of antiviral drugs was not related to GIT bleeding in COVID-19 patients.Keywords: antiviral drugs, Â COVID-19, gastrointestinal tract bleeding